Risk factors for established vertebral fractures in Japanese patients with rheumatoid arthritis: Results from a large prospective observational cohort study. Issue 3 (May 2015) - Ishida, Osamu; Furuya, Takefumi; Inoue, Eisuke; Ochi, Kensuke; Ikari, Katsunori; Taniguchi, Atsuo; Yamanaka, Hisashi; Momohara, Shigeki
Abstract Objective. The aim of this study was to evaluate the associations between potential risk factors and the occurrence of established vertebral fractures in Japanese patients with rheumatoid arthritis (RA). Methods. A total of 10, 469 patients with RA were enrolled in a prospective, observational study from 2000 to 2011. Self-reported vertebral fractures were verified using patient's medical records and radiographs. Cox proportional hazards models were used to analyze independent contributions of various risk factors for established vertebral fracture occurrence. Results. During a mean follow-up of 5.8 years, established vertebral fractures in 170 patients were verified with medical records and radiographs. Multivariate Cox regression analyses estimated that the hazards ratios of sustaining vertebral fractures increased by 1.84 for female gender, 1.72 for every 10 years of increased age, 1.26 for Disease Activity Score in 28 joints (DAS28), 1.44 for Japanese Health Assessment Questionnaire-Disability Index (J-HAQ-DI), 2.21 for history of any previous fractures, and 1.09 for daily prednisolone dose (mg/day). Conclusion. We confirmed the associations between vertebral fractures and advanced age, J-HAQ-DI, and high daily prednisolone dose; and found significant correlations between vertebral fractures and female gender, DAS28, and history of any previous fracture in Japanese RA patients.